Fundamentals of Laparoscopic Surgery: A Surgical Skills Assessment Tool in Gynecology - Hur, Hye-Chun (Society of Laparoendoscopic Surgeons, 2011)
OBJECTIVE: To describe our experience with the Fundamentals of Laparoscopic Surgery (FLS) program as a teaching and assessment tool for basic laparoscopic competency among gynecology residents. METHODS: A prospective observational study was conducted at a single academic institution. Before the FLS program was introduced, baseline FLS testing was offered to residents and gynecology division directors. Test scores were analyzed by training level and self-reported surgical experience. After implementing a minimally invasive gynecologic surgical curriculum, third-year residents were retested. RESULTS: The pass rates for baseline FLS skills testing were 0% for first-year residents, 50% for second-year residents, and 75% for third- and fourth-year residents. The pass rates for baseline cognitive testing were 60% for first- and second-year residents, 67% for third-year residents, and 40% for fourth-year residents. When comparing junior and senior residents, there was a significant difference in pass rates for the skills test (P=.007) but not the cognitive test (P=.068). Self-reported surgical experience strongly correlated with skills scores (r-value=0.97, P=.0048), but not cognitive scores (r-value=0.20, P=.6265). After implementing a curriculum, 100% of the third-year residents passed the skills test, and 92% passed the cognitive examination. CONCLUSIONS: The FLS skills test may be a valuable assessment tool for gynecology residents. The cognitive test may need further adaptation for applicability to gynecologists.